1999
DOI: 10.1136/bmj.318.7189.972
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a drug overdose in a television drama on presentations to hospital for self poisoning: time series and questionnaire study

Abstract: Objectives To determine whether a serious paracetamol overdose in the medical television drama Casualty altered the incidence and nature of general hospital presentations for deliberate self poisoning. Design Interrupted time series analysis of presentations for self poisoning at accident and emergency departments during three week periods before and after the broadcast. Questionnaire responses collected from self poisoning patients during the same periods. Setting 49 accident and emergency departments and psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
5

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(102 citation statements)
references
References 16 publications
1
96
0
5
Order By: Relevance
“…3 2 Media portrayal of deliberate self-harm has been associated with an increased risk of hospital attendance following deliberate self-poisoning. 83 Careful follow-up of any suicidal youth is important and research suggests that the majority of such youth may not receive adequate follow-up management that then increases the risk of eventual suicide. 1,50,[84][85][86][87][88] …”
Section: Prevention Of Suicidementioning
confidence: 99%
“…3 2 Media portrayal of deliberate self-harm has been associated with an increased risk of hospital attendance following deliberate self-poisoning. 83 Careful follow-up of any suicidal youth is important and research suggests that the majority of such youth may not receive adequate follow-up management that then increases the risk of eventual suicide. 1,50,[84][85][86][87][88] …”
Section: Prevention Of Suicidementioning
confidence: 99%
“…When a popular UK programme (BBC's Casualty, with 15.5 million viewers) featured a rapidly fatal paracetamol overdose, this had no impact on regional parasuicide trends (Simkin et al, 1995). However, using similar methods, a later study found that national rates of paracetamol poisoning doubled when the same programme showed the serious consequences of paracetomol overdose in an RAF pilot (Hawton et al, 1999). There are further methodological problems in researching the effects of violence.…”
Section: Box 2 What Makes Something Newsworthy?mentioning
confidence: 99%
“…There may be potential for educational initiatives highlighting this aspect of paracetamol toxicity, although it is possible that this may have a reverse effect (e.g. an episode of a popular television drama featuring a fatal paracetamol overdose was followed by an increase in similar overdoses among viewers 89 ).…”
Section: Studies To Evaluate the Impact Of The 1998 Uk Legislation Rementioning
confidence: 99%